Genotyping and antibiotic resistance of thermophilic Campylobacter isolated from chicken and pig meat in Vietnam. Issue 1 (December 2016) - Nguyen, Tuan; Hotzel, Helmut; El-Adawy, Hosny; Tran, Hanh; Le, Minh; Tomaso, Herbert; Neubauer, Heinrich; Hafez, Hafez
Abstract Background Campylobacter species are recognized as the most common cause of foodborne bacterial gastroenteritis in humans. In this study nineCampylobacter strains isolated from chicken meat and pork in Hanoi, Vietnam, were characterized using molecular methods and tested for antibiotic resistance. Results The nine isolates (eightC. jejuni and oneC. coli ) were identified by multiplex PCR, and tested for the presence or absence of 29 gene loci associated with virulence, lipooligosaccharide (LOS) biosynthesis and further functions.fla A typing, multilocus sequence typing and microarray assay investigation showed a high degree of genetic diversity among these isolates. In all isolates motility genes (fla A, fla B, flh A, fli M), colonization associated genes (cad F, doc B), toxin production genes (cdt A, cdt B, sec D, sec F), and the LOS biosynthesis genepgl B were detected. Eight gene loci (fli Y, vir B11, Cje1278, Cj1434c, Cj1138, Cj1438c, Cj1440c, Cj1136) could not be detected by PCR. A differing presence of the gene locicia B (22.2 %), Cje1280 (77.8 %), doc C (66.7 %), andcgt B (55.6 %) was found.iam A, cdt C, and the type 6 secretion system were present in allC. jejuni isolates but not inC. coli .fla A typing resulted in five different genotypes withinC. jejuni, MLST classified the isolates into seven sequence types (ST-5155, ST-6736, ST-2837, ST-4395, ST-5799, ST-4099 and ST-860). The microarray assay analysis showed a high genetic diversity within VietnameseCampylobacter isolates which resulted in eight different types forC. jejuni . Antibiotic susceptibility profiles showed that all isolates were sensitive to gentamicin and most isolates (88.8 %) were sensitive to chloramphenicol, erythromycin and streptomycin. Resistance rates to nalidixic acid, tetracycline and ciprofloxacin were 88.9, 77.8 and 66.7 %, respectively. Conclusions To the best of our knowledge, this study is the first report that shows high genetic diversity and remarkable antibiotic resistance ofCampylobacter strains isolated from meat in Vietnam which can be considered of high public health significance. These preliminary data show that large scale screenings are justified to assess the relevance ofCampylobacter infections on human health in Vietnam.